Concepções acerca das práticas inovadoras e educação ambiental na Escola Municipal João Germano Machado, São Francisco do Sul, SC - Moraes, Juliano Ferreira de, 1981- (2020)
Orientador: Prof. Dr. Christiano Nogueira